Crowd and group simulation with levels of detail for geometry, motion and conversational behaviour - CASSELL, JUSTINE; VILHJALMSSON, HANNES; PETERS, CHRISTOPHER; LEESON, WILLIAM; GIANG, THANH; DINGLIANA, JOHN; DOBBYN, SIMON; O'SULLIVAN, CAROL ANN (My University, 2002)
Work on levels of detail for human simulation has occurred mainly on a geometrical level, either by reducing the numbers of polygons representing a virtual human, or replacing them with a two-dimensional imposter. Approaches that reduce the complexity of motions generated have also been proposed. In this paper, we describe ongoing development of a framework for Adaptive Level Of Detail for Human Animation (ALOHA), which incorporates levels of detail for not only geometry and motion, but also includes a complexity gradient for natural behaviour, both conversational and social.
PUBLISHED
Keywords: crowd simulations; computer graphics